(untitled) (Jurnal Pilar Nusa Mandiri, 2021)
Semester Learning Plan (RPS) is a learning planning document prepared as a guide for lecturers and students in carrying out teaching and learning activities on campus for one semester. RPS was made to guide lecturers and students in the learning process so that the material taught is following the learning outcomes set by the study program. To meet and adjust the needs of graduate users and the development of science and technology, the RPS must be regularly reviewed and updated if there are changes in teaching materials that are no longer following current conditions. However, what often becomes a problem is that there is no documented process for changing the RPS content regarding the reasons and which parts have changed so that the RPS change process cannot be carried out at will and when audited there is a history of changing the data. Because of these problems, this research will design and build a web-based RPS management information system that can assist study programs in documenting RPS changes and making it easier for users to access the changed content. The system development method used in this study uses the waterfall method, and for its design using UML (Unified Modeling Language). The final result of this research is a web-based RPS management information system using the Codeigniter 4 framework which can make it easier for managers and users to obtain RPS information.